Service Capability In Meeting Irrigation Water Availability At Cengklik Reservoir - Dyah Julia Syifa; Sri Sangkawati; Hari Nugroho (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
Cengklik Reservoir, located in Boyolali Regency, is mainly used to supply water for irrigation. However, changes in hydrological conditions and increasing irrigation water demand have created an imbalance between available water and irrigation needs. This study aims to evaluate the reservoir's ability to meet irrigation water demand and assess the performance of the irrigation network. The F.J. Mock method was used to estimate the dependable discharge, which had an average value of 0.338 m³/s. In addition, water from the Watuleter Supplementary Supply was considered as an extra source, providing an average discharge of 0.296 m³/s. The irrigation system serves an area of 1,460 ha with a rice–rice–secondary crop planting pattern, requiring an average irrigation water demand of 1.239 m³/s. The water balance analysis showed a surplus during seven periods, although water deficits still occurred in the remaining periods. The recommended alternative was to change the planting pattern to rice–secondary crop–secondary crop, which increased the number of surplus periods to 16, compared with the existing condition. The irrigation network performance assessment showed a score of 65.55% under existing conditions, while the proposed planting pattern improved the score to 68.93%. Although the performance improved, it still fell into the poor category. Therefore, better operation and maintenance are needed to improve the effectiveness of irrigation services.